Community councils and community social management - Pinho De Oliveira, María Fátima (2016)
Social management has been defined as the construction of various spaces for social interaction. It is in these local spaces that opportunities open up between the problems/needs and the communities, and therefore they —the spaces— are a more suitable area for social management intervention. This paper aims to present the theoretical aspects of how community social management acts in favor of Community Councils.